Effect of minerals admixtures on high-performance concrete: C-S-H formation and physical-mechanical properties. - Rivera Torres, Jorge Maurilio (2018)
In order to improve the environmental impact of concrete, there is a global trend to replace Portland cement by minerals admixtures. In addition to the reduction in the environmental impact of the material, the incorporation of supplementary cementitious materials in concrete will densify the cementitious matrix and consequently improve its impermeability, a property associated with the durability and the service life of concrete. However, in most cases, the performance of a cementitious material is typically evaluated through the impact on the mechanical properties and the cost, leaving aside the durability and the effects at the microstructural level. This work intends to study the effect of supplementary cementitious materials on formation of C-S-H and the development of the concrete microstructure. The effect of this development on mechanical properties and durability is evaluated. In this investigation, concretes with water/binder ratio of 0,45 and 0,35, where Portland cement is replaced by natural pozzolan or fly ash in dosage of 20% and 60% by mass of each material where used. The experimental results indicate that the incorporation of natural pozzolan with a dosage of 60% leads to the production of concretes extremely resistant to the chloride ingress without a significant decrease in the compressive strength and modulus of elasticity (11% and 10% respectively at 90 days). The paste analysis by nanoindentation in joint with the qualitative Energy-Dispersive Spectroscopy (NI-EDS) reveal that the physical and mechanical properties of concrete with natural pozzolans are originated from an optimal combination of aluminumcontaining hydrated products, a predominant phase of C-(A)-S-H and a well distributed small hard anhydrous inclusions. While the compressive strength and the modulus of elasticity in plain Portland cement concretes depend mainly on the formation of calcium silicate hydrates.